5-Bromo-1H-indole-3-carbaldehyde 3-methoxy-benzoylhydrazone - Ali, Hapipah Mohd; Ng, S.W.; Halim, A.; Nadiah, S. (International Union of Crystallography, 2005)
Molecules of 5-bromo-1H-indole-3-carbaldehyde 3-methoxy-benzoylylhydrazone, C17H14BrN3O2, are paired by aminocarbonyl hydrogen bonds over a center of inversion, and adjacent pairs are further linked by hydrogen bonds into ribbons. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.